Lebanese medical students’ intention to deliver smoking cessation advice - Jradi, Hoda (J Epidemiol Glob Health, 2015)
Objectives: Objectives of this study were to examine the constructs of the Theory of Planned Behavior and determine how they predict Lebanese medical students’ behavioral intention to advise patients to quit smoking. Study design: This was a cross-sectional study conducted among 191 medical students from six medical schools in Lebanon. Methods: The instrument contained scales that measured attitudes toward the behavior, behavioral beliefs, subjective norms, and perceived behavioral control. Psychometric properties of the scale were examined. Item to total scale score correlations were determined and linear regression was conducted to predict the intention to advise smokers to quit. Results: Respondents had a positive, but not very high, intention to deliver smoking cessation advice. Students reported a positive attitude toward advising patients to quit cigarette smoking and a strong belief in the physician’s obligations in smoking cessation advising. The majority reported lack of time to provide smoking cessation advice, insufficient knowledge of pharmacological aids, and the lack of openness of the patient to receive the advice. The attitude scale was the only variable that yielded a significant prediction of the intended behavior. Conclusions: The construct of attitude toward the behavior appeared to be the most predictive of the intention to deliver advice to quit smoking among Lebanese medical students. Focusing training efforts on this construct could improve the rate of delivery of brief cessation counseling.